La estructura como elemento potenciador de la organización criminal y su importancia en la delimitación con la banda criminal - Baquerizo Santillán, Bryan Jesús (2023)
With the enactment of Legislative Decree No. 1244, Peruvian criminal legal system incorporated two new criminal offenses to fight against organized crime: the crime of criminal organization and the crime of criminal gang, provided for in articles 317 and 317-B of the Criminal Code. The typical wording used by the legislator was deficient, thus generating problems of hermeneutic interpretation regarding the difference between the two types of crime. Based on this, as an answer to this question, this paper proposes the interpretation of the structural element as an exclusive component of the crime of criminal organization and as an enhancer of elements that are also present in the crime of criminal gang, although in a simple formulation in the latter offense.